EVALUASI PENERIMAAN PENGGUNA APLIKASI ADONAI DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) (INTI Nusa Mandiri, 2025)
The Adonai application is designed to make it easier to submit insurance and claims for customers by Kosppi employees, but the level of acceptance still needs to be researched. This research uses the Technology Acceptance Model (TAM) to evaluate the influence of perceived usefulness (9.92%) and perceived ease of use (35.04) on application acceptance. Analysis of data from 53 respondents shows that the two variables simultaneously contribute 66.8% to application acceptance. The results of this research support the validation of TAM as a technology evaluation model in the financial services sector and provide practical recommendations to increase the ease of use and benefits of the adonai application.
Keywords: adonai application; perceived ease of use; perceived usefulness; technology acceptance; Technology Acceptance Model